Jumlah Spora dan Genus Endomikhoriza pada Tanah Monokultur dan Tumpangsari Jeruk Siam (Citrus nobilis Tan.) dengan Tanaman Sayuran di Desa Sekaan Kecamatan Kintamani - CHARLES ALEXANDER YAWAN; ANAK AGUNG ISTRI KESUMADEWI; I WAYAN DANA ATMAJA (Fakultas Pertanian Universitas Udayana, 2017)
The Spores and Genus Number of Endomikoriza on soil of Citrus Orchard Soil in Monoculture (Citrus nobilis Tan.) and Intercrops with Vegetables in Sekaan Districts Kintamani. Endomycorrhiza is a wide spread fungi that develop symbiotic association with numerous plant types except for Brassicaceae and Chenopodiaceae. Endomycorrhizal fungi colonized plants through spore or hypha propagation. The spore number of endomycorrhiza was studied in the soil of orange orchard in the Bali’s center of orange fruit production located in Sekaan Village, Bangli District during November 2015 – January 2016. The orange plants were cultivated in monoculture and intercropped with the following vegetable crops : cucumbers (Cucumis sativus L), tomatoes (Solanum lycopersicum), mustard greens (Brassica rapa subsp. Pekinenshis), and cabbage (Brassica oleracea var. capitata). Three replications of soil samples were taken purposively and separately proceed for laboratory analysis. The following parameters were measured: total spore number and genus types of endomycorrhiza, the content of soil available-P, soil pH, and soil organic-C. The experiment result showed that monoculture system had significant higher number of VAM spores (347 spores) compared to intercropping (178 – 224 spores). Most of VAM spore had small size ranging on 45 – 105 ?m (60,80%) followed by 106 – 249 ?m (33,82%) and the least were ? 250 ?m spores. There were two MVA genus present in the soil of both cropping patterns which grouped to Acaulospora (3 morphotypes) and Glomus (11 morphotypes). The highest number of VAM spores belongs to Glomus.The soil properties that closely related to VAM spore number was soil pH (=0.66**).